2003
DOI: 10.1161/01.atv.0000087141.05044.1f
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Oral and Transdermal Estrogen/Progesterone Regimens on Sensitivity to Activated Protein C Among Postmenopausal Women

Abstract: Objective-Activated protein C (APC) resistance not related to the factor V Leiden mutation is a risk factor for venous thrombosis. Oral estrogen replacement therapy (ERT) has been reported to induce APC resistance. Little is known about the effect of transdermal estrogen. Methods and Results-We enrolled 196 postmenopausal women who were randomly allocated to receive either 1 mg 17␤-estradiol orally (nϭ63) or 50 g 17␤-estradiol transdermally per day (nϭ68), both associated with 100 mg progesterone daily or plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
94
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 158 publications
(106 citation statements)
references
References 39 publications
5
94
0
6
Order By: Relevance
“…29 In addition, 2 randomized controlled trials have shown that oral but not transdermal estrogen, both combined with micronized progesterone, induced an activated protein C resistance. 30,31 Thus, hemostatic data, together with the results of the ESTHER study, suggest that transdermal estrogen combined with micronized progesterone is safe with respect to VTE risk. Similarly, recent data showing that chlormadinone acetate, a pregnane derivative, has little or no effect on blood coagulation and fibrinolysis 32 are consistent with the absence of increased VTE risk among postmenopausal women using transdermal estrogen combined with pregnane derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…29 In addition, 2 randomized controlled trials have shown that oral but not transdermal estrogen, both combined with micronized progesterone, induced an activated protein C resistance. 30,31 Thus, hemostatic data, together with the results of the ESTHER study, suggest that transdermal estrogen combined with micronized progesterone is safe with respect to VTE risk. Similarly, recent data showing that chlormadinone acetate, a pregnane derivative, has little or no effect on blood coagulation and fibrinolysis 32 are consistent with the absence of increased VTE risk among postmenopausal women using transdermal estrogen combined with pregnane derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…13 In addition, an acquired resistance to activated protein C has been demonstrated in users of oral estrogen, 14 but 2 randomized trials recently indicated that these results did not apply to users of transdermal estrogen. 15,16 Thus, oral estrogen may impair the balance between procoagulant factors and antithrombotic mechanisms, whereas transdermal estrogen appears to have little or no effect on hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for the distinct VTE risk profile following the two routes of administration involves the first-pass effect of oestrogen. This was shown to affect the synthesis of various oestrogen-dependent hepatic serum factors (Kuhl, 2005), including coagulation and fibrinolysis factors, resulting in blood coagulation activation (Scarabin et al, 1997;Vehkavaara et al, 2001), increased thrombin generation or induction of resistance to activated protein C (Hemelaar et al, 2006;Oger et al, 2003). However, the precise mechanisms by which these changes occur are still unclear.…”
Section: Venous Thromboembolism Risk and Hrtmentioning
confidence: 99%